Reproductive problems in crossbred cattle in central Ethiopia - Bekele, T.; Kasali, O.B.; Alemu, T. (Elsevier, 1991)
Evaluates the reproductive performance of four randomly selected farms of the Dairy Development scheme (Ethiopia). Examines calving interval, calving to conception interval, no. of services per conception, percentage of animals found positive for various reproductive disorders, and parity, season and year effects on abortion rate.